Enhanced antioxidant activity of okara through solid state fermentation of GRAS Fungi - Azis Boing SITANGGANG; Wenny Silvia Loren SINAGA; Felicia WIE; Franz FERNANDO; Warawut KRUSONG (My University, 2019)
The enhancement of antioxidant activity of fermented okara was investigated using fungal solid-state fermentation. The initial fungal concentration and water activity were found to influence the enhanced antioxidant capacity of fermented okara. Extracellular enzymes, especially proteases and carbohydrases might facilitate the hydrolysis of okara protein that yielded antioxidative amino acids and peptides, as well as the release of isoflavones-derived components. Fermentation of okara with R. oligosporus with 1.04×10-3 gDCW/gokara as initial concentration, water activity of 0.931 was found to yield the highest antioxidant strength. Whereas for A. Oryzae, 1.6×10-3 gDCW/gokara was optimum as the initial concentration with water activity of 0.913. With these optimum conditions, solid-state fermentation of okara could enhance the antioxidant activity up to 2.6- and 5.5-fold, respectively for R. oligosporus and A. oryzae. Besides having an enhanced antioxidant activity, the fermented okara also had higher protein content, amino nitrogen content, and protein digestibility.
Keywords: Rhizopus oligosporus; Solid-State Fermentation; Protein Hydrolysis and Bioactive Peptides